La técnica del comentario y el pensamiento crítico en estudiantes de la institución de formación docente Indoamérica de Trujillo - Martos Medina, Alejandro Marcial (2019)
ABSTRACT The purpose of investigation constitutes the application of the technique of comment to develop the critical thought of the students in the area Social Sciences of Comunicación's business career, of Formación Docente Indoamérica's Institute ”. Investigation sustains itself in the principles of Robert Ennis's, Peter Facione's, Richard Paul's, Boisvert's theoreticians, Vygotsky and Asubel; I eat those who coincide in highlighting that the critical thought is in effect itself necessary in the world present-day. The bibliographic study confirms the still development of this educational technique with which once the pedagogic proposal was based. The quantitative measurement confirms the development of the critical thought of the students, is older in the experimental group with a 50 % in the level of achievement of capacities.